(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
This study aimed to characterize the final action within the current political breakdown of traditional ideological speeches. This identified the basic characteristics of the current political discourse to show its application in the current political action, we examined the state of affairs of some political unrest in Venezuela located to determine consistency with the governing political speech and finally examined the effect of ideological discourses in political action to show their relationship in the management, exercise and maintenance of power. The methodology used was based on the category of qualitative research, so that the researcher takes on the characteristics and risks involved in such research and the researcher is the instrument of measurement, because the prevailing view thereof; are small-scale intensive studies, they have no intention to test a specific hypothesis, but rather to generate ideas to develop new hypotheses or theories. Addressed at the conclusion of the current shortcomings and stable political solutions concerning the use of discursive and instrumental arguments for access and maintenance of power as an exercise in hegemony.